If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 1) = -8 Reorder the terms: (1 + 3x) = -8 Remove parenthesis around (1 + 3x) 1 + 3x = -8 Solving 1 + 3x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = -8 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = -8 + -1 3x = -8 + -1 Combine like terms: -8 + -1 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| 0=-12+3x | | (3x)2=100 | | 0.37(28+67.7k)=56.758 | | (93x-109)/17*5=515 | | 7-3(2x-1)=2x+26whatisx | | 10-2x=3x-10 | | 2w+4*w=48 | | 5x+24=x-8 | | -8x+6=3x+21 | | 3/4d-6=9 | | -39=6x-3(-x-2) | | -15.5+19a=-4(-5a+3) | | Y-36=36 | | 2x+114+2x+58=180 | | 6x+24+6x+0=96 | | 72/8*3=f | | 12x+108= | | -1-2x=-5 | | -8x+6=-3x-26 | | 72/8/3=f | | 9x-61+6x+9=158 | | (2)(6)(x+9)= | | 9x-61+6x+9=90 | | 3*7w+60=5*5w | | 9x-61+6x+9=180 | | f*8/3=72 | | 2(5x)=x+3+33 | | 9x-17+4x+55=90 | | 2x-4y+6z=-8 | | 16y^2-24y^1+9y=0 | | 4x+21+3x+48=180 | | 2(x-3)+5x=3(2x-1) |